MEASURES TO CONTROL AGAINST FUSARIUM MAIZE DISEASE (Academicia Globe: Inderscience Research, 2023)
The article considers measures to combat Fusarium, which damages the development and productivity of corn. The experiments were carried out at the Southern Research Institute of Agriculture.